2006
DOI: 10.1002/app.22782
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of poly(butylene terephthalate)/montmorillonite nanocomposites

Abstract: ABSTRACT:The melt intercalation method was employed to prepare poly(butylene terephthalate) (PBT)/montmorillonite (MMT) nanocomposites, and the microstructures were characterized with X-ray diffraction and transmission electron microscopy. Then, the nonisothermal crystallization behavior of the nanocomposites was studied with differential scanning calorimetry (DSC). The DSC results showed that the exothermic peaks for the nanocomposites distinctly shifted to lower temperatures at various cooling rates in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 31 publications
6
40
0
Order By: Relevance
“…[2][3][4][5][6] In recent years, isothermal or nonisothermal crystallization kinetics of PBT blends and composites has also been studied. [7][8][9][10][11] Wu et al 12 studied the nonisothermal crystallization kinetics of PBT/organo-montmorillonite nanocomposites by differential scanning calorimetry (DSC) method. They reported that small amounts of clay (1 wt %) could accelerate the crystallization process, whereas higher clay loadings reduced the rate of crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In recent years, isothermal or nonisothermal crystallization kinetics of PBT blends and composites has also been studied. [7][8][9][10][11] Wu et al 12 studied the nonisothermal crystallization kinetics of PBT/organo-montmorillonite nanocomposites by differential scanning calorimetry (DSC) method. They reported that small amounts of clay (1 wt %) could accelerate the crystallization process, whereas higher clay loadings reduced the rate of crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, PNs based on pure polymeric matrices, such as polyamides, [3,4] polyolefins, [5] polyesters, [6][7][8][9] and other engineering thermoplastics, [10] have been studied. When dispersion is difficult to achieve in the pure matrix, chemical modification of the matrix [11] has been carried out with the aim of ameliorating the compatibility with the organoclay.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties and the morphology of recycled PET, [9,16,17] and the toughening by rubber addition [18] have been studied, as well as the effect of organoclay addition on nucleation [19] and the enhancement of barrier properties. [20] In the case of poly(butylene terephthalate) (PBT)-based PNs, the clay acted as a heterogeneous nucleating agent at low content [8] but as a physical hindrance to retard crystallization at high content. [21] A surfactant with medium polarity [22] or with hydroxyethyl terephthalate groups [23] led to large dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…For many polymers including polypropylene [18][19][20], polyoxymethylene [21], poly(ethylene terephthalate) [22], poly(butylene terephthalate) [23], poly(butene-1) [24], but in particular polyamides [25][26][27][28][29][30][31][32][33][34], it has been shown that addition of nanofillers often enhance crystallization and even support the formation of specific crystal polymorphs. In fewer cases, however, a retardation of the crystallization process has also been reported, likely due to an immobilization of polymer chain segments at the polymer/nanofiller interface [35,36].…”
Section: Introductionmentioning
confidence: 99%